"Turn on" orange fluorescent probe based on styryl-BODIPY for detection of hypochlorite and its application in live cell imaging. (March 2019) - Jantra, Suthikorn; Butta, Patcharavadee; Jithavech, Ponsiree; Rojsitthisak, Pornchai; Palaga, Tanapat; Rashatasakhon, Paitoon; Sukwattanasinitt, Mongkol; Wacharasindhu, Sumrit
Abstract: Fluorescent probes are great tools for visualization and imaging of reactive oxygen species (ROS) in living cells. Although several probes perform well with green emission, however, to maximize tissue penetration and minimize interference from auto-fluorescence, a probe with longer wavelength is desirable. In this study, boron-dipyrromethene (BODIPY)-based fluorescent probeSB2 with high cell penetration and ROS selectivity, has been developed for detection of intracellular ROS.SB2 has two styryl groups anchored to the BODIPY pyrrole rings to extend the emission wavelength into the red region (657 nm) and also to act as a new receptor for ROS. In aqueous media, the probe demonstrated colorimetric change from blue to purple and orange fluorescence turn-on at 590 nm, selectively to hypochlorite, with the detection limit of 0.26 μM. The several oxidative intermediates were observed by mass spectrometry. Fluorescence detection withSB2 of endogenous ROS, in RAW264.7 macrophages, induced by lipopolysaccharide (LPS) or addition of exogenous NaOCl was observed in the orange field (570–620 nm). Graphical abstract: Highlights: A novel orange BODIPY-based probeSB2 for hypochlorite detection based on oxidation of styryl groups has been prepared. TheSB2 displayed colorimetric change from blue to purple and fluorescence turn-on at 590 nm, selectively to hypochlorite. In vivo fluorescence imaging withSB2 induced by lipopolysaccharide or addition of NaOCl is observed in the orange field.